2008
DOI: 10.1080/10495390701880946
|View full text |Cite
|
Sign up to set email alerts
|

SNiPORK – A Microarray of SNPs in Candidate Genes Potentially Associated with Pork Yield and Quality – Development and Validation in Commercial Breeds

Abstract: SNiPORK is an oligonucleotide microarray based on the arrayed primer extension (APEX) technique, allowing genotyping of single nucleotide polymorphisms (SNPs) in genes of interest for pork yield and quality traits. APEX consists of a sequencing reaction primed by an oligonucleotide anchored with its 5' end to a glass slide and terminating one nucleotide before the polymorphic site. Extension with one fluorescently labeled dideoxynucleotide complementary to the template reveals the polymorphism. Ninety SNPs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…With the advent of genome-wide panels of single nucleotide polymorphisms (SNPs), SNPs have been widely used for the detection and localization of QTL for complex traits in many species [7], and have proved powerful and useful in identification of casual mutations associated with economically important traits in livestock [8], [9], [10], [11], [12], [13], [14], [15] as well as human diseases [16], [17], [18], [19]. Most recently, along with maturing of genome sequencing and high throughput SNP genotyping technologies, genome-wide association studies (GWAS) are becoming practical for exploring genes associated with complex traits.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of genome-wide panels of single nucleotide polymorphisms (SNPs), SNPs have been widely used for the detection and localization of QTL for complex traits in many species [7], and have proved powerful and useful in identification of casual mutations associated with economically important traits in livestock [8], [9], [10], [11], [12], [13], [14], [15] as well as human diseases [16], [17], [18], [19]. Most recently, along with maturing of genome sequencing and high throughput SNP genotyping technologies, genome-wide association studies (GWAS) are becoming practical for exploring genes associated with complex traits.…”
Section: Introductionmentioning
confidence: 99%
“…The mean of drip loss in this study was 2.76% which indicated this was normal meat. A previously study revealed that the polymorphism A2991C of CYP21 gene discovered by Kami nski et al (2008) with bioinformatics approach is localized in the putative intron splicing site, suggesting possible influence on mRNA stability and CYP21 biosynthesis efficiency. A previously study revealed that the polymorphism A2991C of CYP21 gene discovered by Kami nski et al (2008) with bioinformatics approach is localized in the putative intron splicing site, suggesting possible influence on mRNA stability and CYP21 biosynthesis efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed that all experimental animals were free from recessive mutation in RYR1 gene (Ryanodine Receptor) known to affect the meatness and meat quality. All fatteners were genotyped in 50 loci (Table 1) by the method described earlier (Kamiński et al, 2008). Whereas allelic frequencies in the loci studied for both breeds are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%